Protection Strategies for Coastal Reclamation in the Guangdong-Hong Kong-Macao Greater Bay Area from the Perspective of Flood Risk - WANG Jiangbo; ZHENG Jiaqi; ZHENG Xiaoyan; GOU Aiping (Haiyang Kaifa yu guanli)
Enclosure is one of the forms of land use for comprehensive land management and water control, which plays a role in flood control and drainage in waterfront areas. At present, global climate disasters are frequent, the risk of floods is increasing, and the demand for land resources for urbanization construction is also rising. The article takes coastal reclamation as its research object. By extracting the spatial structure of coastal reclamation in the Guangdong-Hong Kong-Macao Greater Bay Area from remote sensing images, it investigates the scale, spatial distribution, reclamation intensity, and land use conversion patterns of coastal reclamation areas. The distribution of enclosed fields is fragmented, and the ability to resist wind and waves is limited; Urban and rural construction land continues to encroach on enclosed land, and the risk of flooding increases. On this basis, the coastal enclosure protection strategy to improve the flood response capacity is proposed from four aspects: zoning protection, regional overall pattern protection, ecological flood control, and improvement of the normative system, so as to provide strategic recommendations for the protection of coastal enclosure in the Greater Bay Area.